Incremental Value of Left Ventricular Mechanical Dyssynchrony Assessment by Nitrogen-13 Ammonia ECG-Gated PET in Patients With Coronary Artery Disease - Zheng, Danzha; Liu, Yanyun; Zhang, Lei; Hu, Fan; Tan, Xubo; Jiang, Dawei; Zhou, Weihua; Lan, Xiaoli; Qin, Chunxia (Frontiers in Cardiovascular Medicine, 2021)
Background: Phase analysis is a technique used to assess left ventricular mechanical dyssynchrony (LVMD) in nuclear myocardial imaging. Previous studies have found an association between LVMD and myocardial ischemia. We aim to assess the potential diagnostic value of LVMD in terms of myocardial viability, and ability to predict major adverse cardiac events (MACE), using Nitrogen-13 ammonia ECG-gated positron emission tomography (gPET). Methods: Patients with coronary artery disease (CAD) who underwent Nitrogen-13 ammonia and Fluorine-18 FDG myocardial gPET were enrolled, and their gPET imaging data were retrospectively analyzed. Patients were followed up and major adverse cardiac events (MACE) were recorded. The Kruskal-Wallis test and Mann-Whitney U test were performed to compare LVMD parameters among the groups. Binary logistic regression analysis, receiver operating characteristic (ROC) curve analysis, and multiple stepwise analysis curves were applied to identify the relationship between LVMD parameters and myocardial viability. Kaplan–Meier survival curves and the log-rank test were used to look for differences in the incidence of MACE. Results: In total, 79 patients were enrolled and divided into three groups: Group 1 (patients with only viable myocardium, n = 7), Group 2 (patients with more viable myocardium than scar, n = 33), and Group 3 (patients with less viable myocardium than scar, n = 39). All LVMD parameters were significantly different among groups. The median values of systolic phase standard deviation (PSD), systolic phase histogram bandwidth (PHB), diastolic PSD, and diastolic PHB between Group 1 and Group 3, and Group 2 and Group 3 were significantly different. A diastolic PHB of 204.5° was the best cut-off value to predict the presence of myocardial scar. In multiple stepwise analysis models, diastolic PSD, ischemic extent, and New York Heart Association (NYHA) classification were independent predictive factors of viable myocardium and myocardial scar. The incidence of MACE in patients with diastolic PHB > 204.5° was 25.0%, higher than patients with diastolic PHB <204.5° (11.8%), but the difference was not significant. Conclusions: LVMD generated from Nitrogen-13 ammonia ECG-gated myocardial perfusion imaging had added diagnostic value for myocardial viability assessment in CAD patients. LVMD did not show a definite prognostic value.